Ultra Wideband Communications Novel Trends - Antennas and Propagation - Matin, Mohammad (IntechOpen, 2011)
This book explores both the state-of-the-art and the latest achievements in UWB antennas and propagation. It has taken a theoretical and experimental approach to some extent, which is more useful to the reader. The book highlights the unique design issues which put the reader in good pace to be able to understand more advanced research.